(untitled) (Journal of Science and Technology, 2016)
Sensitivity analysis was carried out for the Rational and Manning formulae the most popular equations used for the design of stormwater drainage system in Ghana. The Return Period and the Runoff Coefficient wore the input parameters for the Rational Formula. the channel Slope, Manning’s Roughness Coefficient, the Depth and Walsh of a concrete U-drain formed the inpur parameters for the Manning’s Equation. The results revealed that the Rational formula is more sensitive to changes in the Runoff Coefficient than equivalent percentage changes at ate Return Period. For the Manning’s Equation it was found out that Ada that channel depth and channel within have a more pronounced effect on the carrying capacity of the channel than the slope and roughness coefficient. Nevertheless, changes in the performance of a channel due to changes in the performance of a channel due to the roughness coefficient and the slope were found to be very significant. Based on these results a strong recommendation is made for regular maintenance of drains